A református egyházszervezet szovjet mintára történő transzformálása Kárpátalján - Szamborovszkyné Nagy Ibolya; Самборовскі-Нодь Ібоя; Ibolya Szamborovszky-Nagy (Károli Gáspár Református Egyetem Hittudományi Kar Egyháztörténeti Kutatóintézet, 2022)
Egy háború utáni átmenettörténet regionális vetülete sajátos felekezeti olvasatban – ezt jelenti az alábbi, tartalmában egyháztörténeti tanulmány. Az a strukturális átalakítás, amelyen a református egyházi szervezet 1946 februárja és 1949 decembere között átesett a szovjetesítés megnyilvánulásának sajátos terepe volt, belőle egyértelműen kirajzolódik a kép, hogy Kárpátalja 1944-es szovjet megszállása milyen mélyreható változásokat indított el a vidéken. Az ideológiája szerint nyíltan ateista állam közvetlenül a terület bekebelezése után még úgy vélte, hogy kellő átalakítást követően fel tudja használni majd a különböző felekezeteket saját érdekeinek elérésére. Ám az egyházközségek autonómiájára épülő, zsinat-presbiteri elv szerint építkező reformátusság semmilyen megközelítés felől sem illett az egyszemélyi diktatúra egyértelműen hierarchikus gondolkodási rendszerébe. Ezért át kellett alakítani, formára igazítani annak egyházszerkezetét. Az átformálásra a szovjet birodalmi bürokrácia számára az általa már ismert Orosz Ortodox Egyház volt a modell. Alábbi írásból a kárpátaljai református egyházszervezet szovjet mintára történő transzformásának folyamata rajzolódik ki, melynek végére eltűntek az egyházmegyék, az esperesek, a püspök és az egyházkerület is.

Abstract. The period from January 1946 to December 1949 was the post-World War II transitional period for the Transcarpathian Reformed Church. In these four years, the notion of Reformation based on the Synod- Presbyterian principle (which had not been well known in the Soviet imperial bureaucracy until then) changed several times. At the beginning of 1946, Reformed people were considered enemies and the president of the Council for the Affairs of Religious Cults in Kiev stated: “the followers of the Reformed Church used to serve in the Hungarian army during the war; thus, their organizations cannot be registered by the state authority”. In response to this statement, the official attitude changed a month later since the Reformed pastors made a declaration at their meeting in Munkács, in which they stated that all Reformed pastors were obliged to obey the higher powers, whom God had ordained, and that they recognized the Soviet government as legitimate over them. Moreover, the officials overlooked and from the background even advocated the possibility of their joining the Russian Union of Evangelical Christians-Baptists. However, during the negotiations, the Soviet state security authorities subjected the Reformed pastors to scrutiny and realized that they had better treat them as a separate denomination, so that they could at least keep an eye on their activities. Thus, in the second half of 1948, two-thirds of the Reformed congregations were officially authorised to operate. In the end, the deliberately unregistered parishes were expected to decline and give up their activities, as eight of their pastors had been arrested and convicted of anti-Soviet activity. Finally, at the end of 1949 – after having abolished the sessions, the presbyteries, and the titles of chief elder, dean and bishop – all registered communities were placed under the authority of a church administrator, the moderator. In this way, the Reformed church organization was transformed into the Soviet model, i.e., it was now (from the point of view of the bureaucracy) structured according to the state hierarchy.
The Transformation of the Reformed Church Organization into the Soviet Model in Transcarpathia
Keywords: magyar reformátusok a Szovjetunióban; kárpátaljai református egyházszervezet; magyar kisebbségek a Szovjetunióban; kommunizmus; Hungarian Reformed people in the Soviet Union; History of the Reformed Church in Transcarpathia; Hungarian minorities in the Soviet Union; church-state relations; communism